Deskripsi Tingkat Pengetahuan Masyarakat Denpasar terhadap Obesitas Lebih Rentan Terinfeksi COVID-19 - Laksmita, Saka (Universitas Muhammadiyah Surabaya, 2023)
COVID-19 is a virus that can spread through direct contact, indirect contact, or close contact with an infected person. This situation makes a person vulnerable to disease. Good knowledge about COVID-19 and healthy living behaviours as an effort to prevent transmission of COVID-19 are essential to implement. The aim is to determine the description of the understanding of the people of Denpasar City related to obesity being more susceptible to COVID-19 infection. This type of research is descriptive by conducting a survey of 400 people in Denpasar City through purposive sampling. This study used a questionnaire as a data collection tool and the data were analyzed univariately. Based on the characteristics of the respondents, it was found that most respondents were in the age range of 21-30 years. For the latest education, most of the respondents are high school / equivalent and university graduates with a percentage of 53.25% and 46% respectively. In terms of occupation, it was found that most of the respondents consisted of students with a percentage of 70.5% and the least were in the TNI / Police / Retired with a percentage of 0.25%. For the characteristics of the place of residence of the respondents, most of them are found in South Denpasar and the least in East Denpasar with a percentage of 32.5% and 16.75% respectively. The majority of respondents knowledge is known that most people in Denpasar understand that people who are obese will be susceptible to COVID-19 infection with good and sufficient percentages of 44% and 53% respectively.Â Based on the results of the research and observations, it can be concluded that the people of Denpasar City have a high level of knowledge about the impact of obesity in relation to COVID-19. Keywords: COVID-19, Level of knowledge, Obesity, Society